WAKAF UANG: TINGKAT PEMAHAMAN MASYARAKAT DAN FAKTOR PENENTUNYA (Studi Masyarakat Muslim Kota Surabaya, Indonesia) - Ekawaty, Marlina; Muda, Anggi Wahyu (IQTISHODUNA, 2015)
The important role of waqf as a source of funds and low Muslim’s awareness on cash waqf collectionversus it potential cash waqf in Indonesia push this study. This study aims to determine the level ofunderstanding of the Muslim societies in Surabaya on cash waqf and the factors that influence it, eitherinternal or external factors. Descriptive statistics, Z test, and multiple regression analysis are used for primarydata collected by distributing questionnaires to the Muslim societies in Surabaya. The results show that themost Muslim do not understand cash waqf. The level of understanding is influenced by by internal andexternal factors. The internal factor is knowledge of religion and the external factor is access to informationmedia. To improve understanding of the Muslim societies about cash waqf needs to increase religiousknowledge and access to information media, either print or electronic media.